D Development of Science Teaching Materials Using the RADEC Model to Improve Higher Level Thinking Abilities of Elementary School Students - Nofia Henita; Ardipal; Desyandri; Zelhendri Zen (Postgraduate, University of Mataram, 2024)
The purpose of this study is to create science teaching materials that use the RADEC model to increase HOTS for grade IV elementary school students. This type of research is development or R&D (Research and Development). The research model applied is a 4-D model, which consists of the stages of definition, design, development, and deployment. The data collection techniques used are observation, interviews and questionnaires. This research was conducted in January 2024 in three elementary schools. The research subjects consisted of 46 elementary school students in grade IV as primary data. The research instrument used was a validation sheet, which was used to test the level of validity of teaching materials by 5 experts, consisting of 3 material experts, 1 linguist, and 1 media expert. The validation results by 5 experts showed a material feasibility score of 95%, language 93%, and media design 89% (all very valid). The practicality of teaching materials is considered very high by teachers (96%) and students (90%). The effectiveness test showed an N-Gain score of 76.1 (effective), with the average Pre-test of 48.7 increasing to 88.23 on the Post-test. In conclusion, this RADEC-based science teaching material is valid, practical, and effective in improving students' HOTS.